INFLUENCE OF IRON-DEFICIENCY ANAEMIA OF MOTHER ON THE ULTRASTRUCTURE OF LIVER OF FETUS AND NEWBORN - Проценко, О.С. (World of Medicine and Biology, 2015)
Electron microscopic studies revealed that the depth and severity of degenerative and destructive processes in the liver cells increases in proportion to the severity of iron deficiency anemia in mother. The ultrastructure of hepatocytes changed with the growth of the severity of iron deficiency anemia from compensatory adaptation to destructive forms. Trigger the development of degenerative and destructive processes in the liver is mitochondrial dysfunction.
Keywords: iron-deficient anaemia; fetus; liver; ultrastructure of hepatocytes; mitochondrial disfunction